The Effect of Internal Migration on Regional Poverty in Turkey: The Determining Role of the Agricultural Sector - Mehmet Zanbak; Reyhan Özeş Özgür (Journal of Economy Culture and Society)
In Turkey, migration and poverty became two intersecting concepts -particularly after the 1990s. A great majority of those groups who live in cities on welfare benefits consist of people who migrated after this period. In this process, while internal migration increased employment pressures, it was also accompanied by a growth in the number of the poor people. This study explores how poverty changed in Turkey especially when people who left the agricultural sector migrated to areas where industry and service sectors were concentrated. The model created to reveal the potential effects of internal migration particularly in the period between 2008 and 2014 in addition to other factors affecting poverty was estimated using the panel data analysis. After the estimation, it was determined that migration originating from areas where agriculture relatively came to the forefront in terms of employment and production reduced the total number of the poor in the country. This finding indicates that leaving the agricultural sector to find a job and turning to industry and service sectors resulted in an income increase and had positive effects in terms of reducing the poverty. It was also found that migration to TR-1 Istanbul (which is among those areas taking the lead in terms of employment capacity), significantly differs from that of other areas in terms of influencing the total number of the poor in the country.